PENGARUH PIJAT OKSITOSIN TERHADAP LAMA PENGELUARAN KOLOSTRUM PADA IBU POST SECTIO CAESARIA DI RSUD KOTA MADIUN - ., Sundari; Sari, Rury Narulita (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Mother Caesaria post section (SC) is often difficult to breastfeed. If the baby does not suck the nipple and a half hours after childbirth, hormone oxytocin and prolactin down so that the milk out on the third day or so. The impact is not smooth spending and milk production can cause problems in the mother and baby. Thus, businesses need to stimulate prolactin and oxytocin one with massage oxytocin. The purpose of this study to determine the effect of oxytocin massage the mother's colostrum spending long post Caesaria section in RSUD Kota Madiun. Type of analytical research quasy Experiment with the draft "posttest only control group design". Population 48 mothers post SC, a large sample of 42 people with purposive sampling techniques are divided into 2 groups, 21 people do massage oksitosun and 21 people do not do. The instrument uses an observation sheet. The results were tested by t-test. Spending long colostrum experimental group 26 respondents. It is known there are 19 people (73,1%) secrete colostrum quickly. Whereas in 7 others (26,9%) slow. While the control group 26 respondents there were 21 (80,8%) secrete colostrum slow. While in 5 others (19,2%) quickly in removing the colostrum. Based on the analysis of statistical test, p = 0.00 <0.05, which means that Ho refused and Ha accepted or was significant effect of oxytocin on the long massage expenditure kolostrum with 0.540 correlation coefficient indicates that the closeness the relationship between the two variables. The conclusion is massage effect of oxytocin on maternal colostrum spending long post Caesaria section in hospitals Madiun. Suggestions for RS, massage can be applied to the mother oxytocin post Sectio Caesaria. Besides mother Caesaria post section can also apply massage oxytocin independently. Keywords: Oxytocin Massage, Colostrum, Sectio Caesaria